2016
DOI: 10.1093/mnras/stw2030
|View full text |Cite
|
Sign up to set email alerts
|

Testing the spherical evolution of cosmic voids

Abstract: We study the spherical evolution model for voids in ΛCDM, where the evolution of voids is governed by dark energy at an earlier time than that for the whole universe or in overdensities. We show that the presence of dark energy suppresses the growth of peculiar velocities, causing void shell-crossing to occur at progressively later epochs as Ω Λ increases. We apply the spherical model to evolve the initial conditions of N-body simulated voids and compare the resulting final void profiles. We find that the mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 51 publications
2
21
0
1
Order By: Relevance
“…This result is consistent with previous studies into the spherical evolution of voids, which found that the largest voids are better approximated by a spherical model than the smallest voids (e.g. Achitouv et al 2015;Demchenko et al 2016). A likely reason for this is that there are many more ways to merge smaller voids to form a lower ellipticity void than a high ellipticity void, and hence a greater number of approximately spheroidal large voids form than approximately ellipsoidal large voids.…”
Section: Shapessupporting
confidence: 91%
“…This result is consistent with previous studies into the spherical evolution of voids, which found that the largest voids are better approximated by a spherical model than the smallest voids (e.g. Achitouv et al 2015;Demchenko et al 2016). A likely reason for this is that there are many more ways to merge smaller voids to form a lower ellipticity void than a high ellipticity void, and hence a greater number of approximately spheroidal large voids form than approximately ellipsoidal large voids.…”
Section: Shapessupporting
confidence: 91%
“…These simulations show the gravitational collapse of dark matter (DM) into a web-like structure, establishing the 'skeleton' for baryonic matter, which falls into the DM's potential well. Within this framework, the growth factor of voids with redshift can be used to constrain the energy density and equation of state parameter of dark energy (DE) (Lavaux & Wandelt 2010;Demchenko et al 2016), which causes the Universe's accelerated expansion. The low density in voids also makes them clean probes of global cosmological parameters, as their interior is less affected by baryonic physics than denser regions (Bos et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Despite ambiguities in their exact definition, it has been observed in simulations that voids are quite spherical [67,68], and therefore it is expected that the spherical expansion model for their abundance must work well (differently from halos, for which spherical collapse alone is not a very good approximation [69]). In this work, we use N-body simulations of ΛCDM as well as fðRÞ and symmetron models of modified gravity in order to identify cosmic voids and study their abundance distribution.…”
Section: Introductionmentioning
confidence: 99%